Cover Chie Vol 9 No 1 - 2021 - Nurjaleka, Lisda; Chie, Journal (Chi'e: Journal of Japanese Learning and Teaching, 2021)
CHI'E Jurnal Pendidikan Bahasa Jepang (Journal of Japanese Learning and Teaching)